The Letter as Presence, Process, and Partnership: Mergers of Message and Medium in the Medieval Initial. (2nd April 2020) - Loic, Erika
Abstract : In light of recent research into the iconicity and materiality of script, I review a particular type of decorated initial that incorporates images of dialogue, authorship, and scribal practice. Monastic scribes reflected on the forms of divine communication by integrating message and medium into their letter designs, many of which were self-reflexive and visually dynamic. Their inventive creations embodied their attitudes towards the written and spoken word as presence (material, corporeal, sacred), process (technical, sensory), and partnership (expressive, interpretative). Following an introduction to the graphic culture of early Christianity, I cover examples that span a period beginning around the year 800 and concluding in the twelfth century, when it became increasingly common for book illuminators to flourish outside of strictly monastic contexts.